Pengaruh jenis pemanis erythritol dan stevia terhadap karakteristik fisikokimia, dan sifat fungsional fruit leather kulit jeruk siam – mangga: The effect of erythritol and stevia sweetener types on physicochemical characteristics, and functional properties of fruit leather siam orange peel - manga - Junaidi, Fahmi; Hermavita, Cindi Dwi; Rismaya, Rina (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2024)
Fruit leather refers to a food item obtained by drying pureed fruit in an oven. Typical raw materials used in fruit leather include nutrient-rich tropical and subtropical fruits, high in dietary fiber and vitamin C. This study aims to explore the impact of erythritol and stevia sweeteners on the physic, physicochemical, and functional characteristics of siam-mango orange peel fruit leather. The study employed a factorial complete randomized design (CRD) with two factors: (1) the treatment of the ratio of citrus peel and mango fruit with concentrations of JM1 (50%: 50%), JM2 (40%: 60%), JM3 (30%: 70%), and JM4 (20%: 80%), and (2) the type of sweetener, specifically erythritol (28%) and stevia (5%). The testing parameters included physical characteristics such as texture and color, chemical characteristics such as moisture, ash, protein, fat, and carbohydrate content, as well as functional properties including vitamin C, reducing sugar, antioxidant, and dietary fiber. According to physicochemical testing, the optimal treatment was achieved using a combination of JM2G2 orange peel 10% and manga 90% (JM2) along with Stevia sweetener type (G2). The physicochemical analysis revealed that the moisture content was 14.52%, ash was 0.933%, protein was 3.73%, fat was 2.875%, and carbohydrate content was 77.945%. As well as analyzing the physical properties and functional effects of food on texture content, this study measured total color value, vitamin C, reducing sugar, and antioxidant activity (IC 50). The results showed that the values for each were 3.5, 49, 13.675%, 27.215%, and IC 50 value: 76.02, respectively. The utilization of erythritol and stevia sweeteners has been shown to impact the quality of fruit leather.